B Part of It study: a longitudinal study to assess carriage of Neisseria meningitidis in first year university students in South Australia. Issue 4 (3rd April 2019) - McMillan, Mark; Walters, Luke; Mark, Turra; Lawrence, Andrew; Leong, Lex E. X.; Sullivan, Thomas; Rogers, Geraint B.; Andrews, Ross M.; Marshall, Helen S.
ABSTRACT: Objectives: N. meningitidis carriage in Australia is poorly understood. This study aimed to estimate prevalence and risk factors for carriage of N. meningitidis in South Australian university students. We also sought to identify whether delayed freezing of oropharyngeal samples altered PCR positivity, cycle threshold, or culture positivity. Methods: Oropharyngeal swabs were taken from first year university students and repeated after 3 months, with risk factor questionnaires completed at both visits. Specimens were subjected to real-time PCR screening for the presence of specific meningococcal DNA. Results: The study enrolled 421 individuals, 259 returned at 3 months. At baseline, 56% of participants were female and 1.9% smokers. Carriage of N. meningitidis at baseline was 6.2% (95% CI, [4.2%, 8.9%]). Visiting a bar more than once a week (OR 9.07; [2.44, 33.72]) and intimate kissing (OR 4.37; [1.45, 13.14]) were associated with increased carriage. After imputing missing data, the point estimate for carriage at 3 months was 8.6% compared to 6.2% at baseline (OR 1.42; 0.91 to 2.20). Recovery of N. meningitidis on selective agar was significantly reduced in cryovials frozen at 48 hours compared to 6 hours (24/26, 92.3% vs. 14/26, 53.9%, p = 0.002). Conclusion: Attending bars and engaging in intimate kissing is associated with oropharyngeal carriage in South Australian university students. Adolescent meningococcal vaccine programs should be implemented at school, prior to increased attendance at bars, intimate contact, and carriage acquisition. Delaying freezing of oropharyngeal specimens longer than 16 hours reduces yield of N. meningitidis by culture but not PCR detection.